Copper metabolism in retinitis pigmentosa. Issue 11 (November 1976) - Gahlot, D K; Khosla, P K; Makashir, P D; Vasuki, K; Basu, N
Abstract : Clinically and electrophysiologically confirmed cases of primary retinitis pigmentosa have been investigated regarding their copper metabolic state. It is observed that these patients show a normal or near normal serum copper concentration, very low plasma caeruloplasmin concentration, and a very high copper urinary excretion. A similarity between this condition and hepatolenticular degeneration is drawn and it is suggested that retinitis pigmentosa may also be a condition caused by an inborn error of copper metabolism.